Adipose Tissue-Derived Stem Cells Have the Ability to Differentiate into Alveolar Epithelial Cells and Ameliorate Lung Injury Caused by Elastase-Induced Emphysema in Mice - Eriko Fukui; Soichiro Funaki; Kenji Kimura; Toru Momozane; Atsuomi Kimura; Ryota Chijimatsu; Ryu Kanzaki; Takashi Kanou; Naoko Ose; Masato Minami; Shigeru Miyagawa; Yoshiki Sawa; et al. (Hindawi Limited, 2019)
Chronic obstructive pulmonary disease is a leading cause of mortality globally, with no effective therapy yet established. Adipose tissue-derived stem cells (ADSCs) are useful for ameliorating lung injury in animal models. However, whether ADSCs differentiate into functional cells remains uncertain, and no study has reported on the mechanism by which ADSCs improve lung functionality. Thus, in this study, we examined whether ADSCs differentiate into lung alveolar cells and are able to ameliorate lung injury caused by elastase-induced emphysema in model mice. Here, we induced ADSCs to differentiate into type 2 alveolar epithelial cells in vitro. We demonstrated that ADSCs can differentiate into type 2 alveolar epithelial cells in an elastase-induced emphysematous lung and that ADSCs improve pulmonary function of emphysema model mice, as determined with spirometry and 129Xe MRI. These data revealed a novel function for ADSCs in promoting repair of the damaged lung by direct differentiation into alveolar epithelial cells.